40. Knowledge and Perception of Cervical Cancer - Elka Halifah; Erna Mutiara; Ria Masniari Lubis (Universitas Syiah Kuala, 2019)
Cervical cancer is a type of cancer which ranks the second of whole incident of cancer in women. Cervical cancer can metastatic to other organs and can cause death. The objective of the research was to knowlage and perception about cervical cancer. The type of research was a survey with descriptive design. The population of women in Banda Aceh and 60 of them were used as the samples using accidental sampling technique. The data were collected by interview and analyzed by using univariat. There were influence of poor knowledge 63,3%, and 75,0% negative perception about cervical cancer. It is recommended that the local Government, Health Office and Indonesian Cancer Foundation in Nanggroe Aceh Darussalam Province provide convenience in service counseling in order to increase knowledge. The movement of early detection program (papsmear) need to be improved so that women sexually active are willing to examine themselves to the health service so that there will be no lateness in having treatment.